Pendidikan Akhlak oleh Orangtua terhadap Anaknya (Studi Kasus Pola Keluarga Sakinah Teladan) di Kalimantan Selatan - Hajiannor, Taufiqurrahman Ahdi Makmur (IAIN Antasari Banjarmasin, 2013)
In the informal education which takes place at home, parents have the central role to consistently educate and shape their children to posses positive traits. To anticipate todayâs development of information and global cultural flows, a matrix of family education which is affiliated to the construction of childrenâs good character becomes urgent. It is hoped that such matrix of family education can be the instrument to filter information and culture. The model ideal family taken as the study sample is the choosen model ideal family that has been selected to represent South Kalimantan in the national level from 2008 to 2012. The selected family is considered to be refresentatif and valid. The result of study points that: the model ideal family has performed a positive character education. It is proved by the fact that the parents have been successful to educate their children.